The Critical Role of Social Capital in Hotel Business Resilience - Ervina, Ersy; Agoes, Adrian (Jurnal Manajemen & Agribisnis, 2022)
The COVID-19 outbreak provides the tourism industry incalculable lessons. Many businesses are concentrating on resilience, but few have explored the potential benefits of social capital. This article explains how utilising social capital might help business hotels boost their resilience during times of crisis. Social capital is inextricably linked to social networks, group collaboration, and trust among internal and external stakeholders. The research conducts in March to August 2021. The data was assessed qualitatively through interviews with four informants from the hospitality industry (Hotel Managers) and hotel associations. According to the research, social capital manifests itself in a variety of ways to assist hotels in times of difficulty. Internally, fighting a pandemic requires a willingness to compromise, with the hotel's leadership and creativity playing a critical role. Externally, the government's and associations' roles have a significant impact on hotel resiliency. Collaboration with associations and other external parties has been demonstrated to assist hotels during times of crises. Social capital cannot be created instantly but must be nurtured from the beginning of the hotel's operations. In turn, the social capital that has been established will ensure the hotel's long-term sustainability facing challenges. Keywords: social capital, hotel resilience, COVID-19, tourism industry, business sustainability